Chapter Cross-linguistic considerations on preverb stacking (with special reference to Bulgarian) - Muro, Alessio (Biblioteca di Studi Slavistici, 2017)
The term preverb stacking (PS) designates the co-occurrence on one verbal base of two or more prefixes bearing spatial, aspectual, or quantificational meanings. The phenomenon is especially productive in Slavic but is also attested in other Indo-European and non-Indo-European languages. This paper provides a first attempt at a cross-linguistic typology of PS. It will also pay attention to problems typical of Slavic (i.e. the interaction of PS and the aspectual value of the verb in terms of the typical Slavic perfective vs. imperfective dichotomy). Special attention will be paid to Bulgarian.